Kekuatan Dan Lendutan Elastis Kolom Semi Pracetak Akibat Beban Aksial Eksentrik (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
This paper present a numerical simulation of four combine of normal-strenght and light-strenght concrete tied column. In this specimens, normal strength used as core concrete and light- strength used as shell concrete. The columns, with normal compressive strength is 23 MPa, and light strength concrete is 10 MPa. The columns had rectangular cross section with total dimension is 290Ã290 mm and the dimension of core concrete is 230Ã230 mm. The columns were subjected to axial and longitudinal loads, with various eccentricity (50 mm, 100 mm, 150 mm, and 200 mm). The columns analyzed with Software Abaqus CAE Student Edition 6.14-2. From the software the result are the elastic load-mide displacement and crack pattern. The analysis showed that the same eccentricity, the maximum axial load of 2.99 column is smaller than the theoretical concrete columns. While the maximum moment concrete column 2.55 less than the theoretical concrete columns. The column stiffness 0.29 kN/m. By using CAE Abaqus Student Edition Software 6.14-2 obtained deflection value of the total of 0.07 m on the eccentricity of 200 mm . And the smallest deflection of 0,031 m on the eccentricity of 50 mm.Keyword: Hybrid concrete compression, eccentricity axial load, Abaqus CAE Student Edition 6.14-2.